Abordagem tridimensional para repensar o processo participativo no planejamento urbano municipal: o caso da Virada Criativa - Sergio Myssior (2020)
In recent decades, the country has experienced important innovations in democratic management and urban participatory arrangements, bringing together hundreds of thousands of people. But the democratic appearance proposed in the participatory processes of municipal urban planning hides an unbalanced system of social representation and effectiveness in the construction of urban policy. Although participatory arrangements are part of the technical and legal requirements for urban planning, the effectiveness of participation, in terms of democratizing capacity, expansion of the role of citizens in decision-making and determination of substantive actions in urban policy, raises the careful analysis of the interaction between the institutional arrangement and participatory design, identifying the limits and paths to broaden the understanding of participatory experiences. The research is based on the premise that democratic management is directly related to the regulatory and socio-political context. And that the participatory process is a heterogeneous and dynamic experience along the way, supported by a multidimensional arrangement that allows the development of values related to inclusion, justice, legitimacy, democratizing capacity and effectiveness of participation. Through semi-structured and oriented interviews according to the multidimensional space of the democracy cube, the case study of Creative Turn, a participatory experience conducted in Belo Horizonte, the research aims to problematize the effectiveness of the participatory process of municipal urban planning, noddedly related to the elaboration of the master plan. The results chart new paths for increasing communication and decision-making, in the use of a participatory and deliberative hybrid system, as well as in expanding the influence of the most relevant decisions of urban policy. The research points to the construction of references for the improvement of the quality of the participatory process, thus allowing a more accurate understanding of the aspects related to inclusion, justice, legitimacy, democratizing capacity and effectiveness of participation.